Temporal Prospects of Persons with Restrictive Quarantine Conditions: Sex and Age Analysis - Virna, Zhanna; Brahina, Kateryna (Psychological Counseling and Psychotherapy, 2020)
The paper presents a theoretical and empirical study of gender and age characteristics of the content of time perspectives of persons who are in restrictive conditions of quarantine. Theoretical substantiation of the importance of forming a coordinated time perspective of the individual for its integration into the social system, includes an analysis of the structural and functional purpose and typological characteristics of time perspectives. The regulatory content of the time-space continuum of the personality in the conditions of deprivation is emphasized and the restrictive conditions of quarantine in the signs of multifunctional deprivation are outlined, which determine the content of the time perspective of the subjects of self-isolation. The purpose of the presented material is a theoretical and empirical study of gender and age characteristics of the content of time perspectives of persons who are in the restrictive conditions of quarantine and substantiation of signs of their life balance. Based on the analysis and theoretical generalization of the problem, a program of individual-oriented survey of persons in self-isolation in connection with the pandemic COVID-19, which includes testing methods and a set of methods for mathematical processing of results. Gender and age differences in the time perspectives of persons in restrictive quarantine conditions were noted: men of all ages are determined by the dominance of the time perspective of the hedonistic-fatalistic present, colored in men from 25 to 50 years by the characteristics of the negative past and transcendent future; and in men over 50 - the characteristics of the transcendent future; women (age range up to 50 years) are determined by the dominance of the time perspective of the future direction, and women over 50 years - the dominance of the time perspective of the negative past. The absence of signs of vital balance of the identified profiles of time perspectives is proved and the main vectors of formation of the optimal profile of time perspective are outlined: the vector of actualization of the future for males and the vector of activation of the present for the studied women.